Workshop on Implementation of Learning on Disability Teaching in the Era of Industrial Revolution 4.0 - Adi Rahadian; Ervan Kastrena; Aziz Amrulloh; Firdaus Hendry Prabowo Yudho; Andi Kurniawan Pratama; Muhamad Syamsul Taufik; Asep Ramdan Afriyuandi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
In this study looking for how much the level of teacher ability in the development of physical education As for the stages of research as follows: (1) Conduct initial identification and analysis of the needs of the object and location of research and conduct preliminary studies, and also literature studies relating to research, (2) Arranging program plans regularly, (3) Arranging instructional, books or activity evaluation tools, (4) Developing research instruments to reveal the ability of physical education teachers in developing Physical Education learning (5) Conducting small group trials to Physical Education teachers; and (6) conducting field trials on physical education teachers. So the conclusion of this research is the experience factor which consists of teaching experience of children with special needs and contact experience with children with special needs. Third, knowledge factors consisting of teacher education background, training, knowledge, and teacher learning needs. Fourth, educational environment factors consisting of resource support, parent and family support, and the school system.